2007
DOI: 10.1577/t06-045.1
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Nonnative Centrarchids in the Upper Colorado River Revealed by Stable Isotope and Microchemical Analyses of Otoliths

Abstract: Nonnative fishes represent a significant impediment to the recovery of imperiled fishes, including those endemic to the Colorado River in the southwestern United States. Efforts to control nonindigenous fish abundance in the upper Colorado River basin have been unsuccessful owing in part to lack of knowledge regarding nonnative fish recruitment sources. We determined the source habitat (floodplain pond versus riverine habitats) for nonnative centrarchid fishes (largemouth bass Micropterus salmoides, green sunf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 38 publications
5
67
0
Order By: Relevance
“…Distinct water  18 O signatures of floodplain lakes and the Mississippi River are likely due primarily to the greater opportunity for evaporative fractionation (Hoefs, 2004) to be expressed in floodplain lakes as a result of their longer water residence times compared to the river. Whitledge et al (2007) observed similar differences in water hydrogen isotopic composition (δ 2 H, which undergoes similar fractionation processes in the hydrologic cycle) between floodplain ponds and the upper Colorado River due to higher evaporation rates of pond water. Persistent differences in water  18 O between the Illinois River and its floodplain lakes have also been documented (Zeigler & Whitledge, 2010).…”
Section: Meanmentioning
confidence: 64%
See 2 more Smart Citations
“…Distinct water  18 O signatures of floodplain lakes and the Mississippi River are likely due primarily to the greater opportunity for evaporative fractionation (Hoefs, 2004) to be expressed in floodplain lakes as a result of their longer water residence times compared to the river. Whitledge et al (2007) observed similar differences in water hydrogen isotopic composition (δ 2 H, which undergoes similar fractionation processes in the hydrologic cycle) between floodplain ponds and the upper Colorado River due to higher evaporation rates of pond water. Persistent differences in water  18 O between the Illinois River and its floodplain lakes have also been documented (Zeigler & Whitledge, 2010).…”
Section: Meanmentioning
confidence: 64%
“…Most classification errors occurred among fish collected from small tributaries of the Mississippi River, although some of these individuals were misidentified as having been locations (Gao et al, 2001;Wells et al, 2003;Brazner et al, 2004;Bickford and Hannigan, 2005;Dufour et al, 2005;Whitledge et al, 2007;Whitledge, 2009). …”
Section: Meanmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace element and stable isotopic compositions of otoliths have been used as natural markers of environmental history for individual fishes in a variety of freshwater environments (Wells et al 2003;Dufour et al 2005;Munro et al 2005;Whitledge et al 2007;Whitledge 2010, 2011;Chapman et al 2013), and represent a potential approach to identify natal environment and larval and juvenile nursery habitats of Bighead Carp and Silver Carp in the Illinois River. Otoliths are calcareous concretions in the inner ear of fishes that contain a permanent record of age and growth and are metabolically inert (Campana and Thorrold 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Association of otolith biochronology with isotopic or elemental composition enables retrospective description of fish environmental history (e.g., identification of natal environment from the portion of the otolith accreted during early life) when an individual has resided in chemically distinct locations for a period of time sufficient to incorporate the signature of those sites (Kennedy et al 2002;Dufour et al 2005;Whitledge et al 2007). Only a few published studies have used otolith chemistry to identify natal environment of invasive fishes in large floodplain river systems.…”
Section: Introductionmentioning
confidence: 99%